IMPLEMENTASI PROFIL PELAJAR PANCASILA DIMENSI MANDIRI PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS VII DI SMP N 2 KOTA JAMBI - Asha Ainul Latifa; Sundari Utami; Yuslistia Opeska (STKIP Subang, 2026)
Education plays a strategic role in shaping character and improving the quality of human resources. One effort to strengthen character in the Merdeka Curriculum is through the implementation of the Pancasila Student Profile, particularly the dimension of independence. This study aims to describe the implementation of the independence dimension in Pancasila Education learning in Grade VII at SMP Negeri 2 Kota Jambi and to identify its supporting and inhibiting factors. The study employed a qualitative approach with a case study design. The research participants included the principal, the Pancasila Education teacher, and Grade VII students. Data were collected through semi-structured interviews, observations, and document analysis. Data validity was ensured through source and technique triangulation, while data analysis was conducted using the interactive model of Miles and Huberman. The results indicate that the independence dimension has been implemented in aspects of self-awareness, self-regulation, and initiative and responsibility in learning. Students have begun to demonstrate awareness of their learning responsibilities, the ability to manage time, and the courage to take initiative in completing tasks. However, the consistency of self-regulation and the self-confidence of some students still need to be strengthened. Supporting factors include a conducive school environment, the support of the Merdeka Curriculum, and participatory teaching approaches. Inhibiting factors include unstable study habits and distractions from gadget use